Fascinating Electrocatalysts with Dispersed Di‐Metals in MN3‐M′N4 Moiety as Two Active Sites Separately for N2 and CO2 Reduction Reactions and Jointly for CN Coupling and Urea Production. Issue 3 (31st January 2023) - Zhu, Changyan; Geng, Yun; Yao, Xiaohui; Zhu, Guangshan; Su, Zhongmin; Zhang, Min
Abstract: The idealized urea electrocatalyst is crucial to boost the CN coupling reaction and simultaneously suppress their isolated reduction process after adsorbing N2 and CO2 molecules. Therefore, the dispersed MN3 ‐M′N4 moiety is investigated systematically, including 26 homonuclear and 650 heteronuclear di‐metal systems. After, 205 stable systems are selected using lowest‐energy principle and ab initio molecular dynamics simulations. According to three possible pathways, NCON, CO, and OCOH to produce urea, a five‐step high‐throughput screening method for excellent catalytic activity and a five‐aspect high‐throughput screening strategy for outstanding catalytic selectivity are proposed, respectively. The potential determined steps and the limiting potential through three pathways are identified. The data indicates both CO pathway and OCOH pathway are more competitive at lower Gibbs free energy. Significantly, the most favorite RuN3 ‐CoN4 combination possesses an extremely low limiting potential of −0.80 V for urea production, meanwhile it exists a strong foundation for experimental preparation. This work not only broadens electrocatalytic potentiality of developing di‐metals as two active sites, but also provides a feasible high‐throughput screening recipe for urea production. Abstract : Three possible reaction pathways for urea production, a five‐step high‐throughput screening method for excellent catalytic activity and a five‐aspect high‐throughput screening strategy for outstanding catalytic selectivity are proposed based on MN3 ‐M′N4 moiety. Finally, RuN3 ‐CoN4 with strong foundation for experimental preparation is identified as the eminent urea electrocatalyst rooted from dispersed di‐metals as two active sites.